2012
DOI: 10.1016/j.febslet.2012.05.054
|View full text |Cite
|
Sign up to set email alerts
|

miR‐376a suppresses proliferation and induces apoptosis in hepatocellular carcinoma

Abstract: MicroRNAs are known to be involved in the pathogenesis of hepatocellular carcinoma (HCC). This study aims to explore the potential biological function of miR-376a, which was found to be inhibited after partial hepatectomy, in HCC. We discovered that miR-376a was frequently down-regulated in HCC cell lines and HCC tissues, while higher relative level of miR-376a was significantly associated with high serum AFP level. Over-expression of miR-376a not only inhibited proliferation but induced apoptosis in Huh7 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 35 publications
6
56
0
Order By: Relevance
“…MicroRNA-376a (miR-376a) has been reported in several human cancers, including upregulation in esophageal cancer tissues, plasma of breast cancer, and downregulation in melanoma, and hepatocellular carcinoma (Zehavi et al, 2012;Zheng et al, 2012;Cuk et al, 2013;Zhao et al, 2013). In particular, Kunte et al found that levels of miR-376a expression were significantly increased with CRC tumor development, using the azoxymethane (AOM)-treated rat model (Kunte et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA-376a (miR-376a) has been reported in several human cancers, including upregulation in esophageal cancer tissues, plasma of breast cancer, and downregulation in melanoma, and hepatocellular carcinoma (Zehavi et al, 2012;Zheng et al, 2012;Cuk et al, 2013;Zhao et al, 2013). In particular, Kunte et al found that levels of miR-376a expression were significantly increased with CRC tumor development, using the azoxymethane (AOM)-treated rat model (Kunte et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It was found in our previous study [3] that miR-376a was frequently down-regulated in human HCC specimens, but the underlying mechanism remains obscure. Knowing that epigenetic alterations can deregulate Dlk1-Dio3 microRNA cluster in epithelial ovarian cancer [7], we wondered whether it was also responsible for the dysregulation of miR-376a in HCC.…”
Section: Resultsmentioning
confidence: 99%
“…Although many studies have described multiple genetic and epigenetic changes in HCC, the current evidence cannot explain the full complexity of HCC [2]. Our previous study demonstrated that miR-376a suppressed the proliferation and induced the apoptosis of HCC cells [3], but little is known about the underlying mechanism of its deregulation in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al reported that miR-376a was downregulated in hepatocellular carcinoma tissues and cell lines and could suppress proliferation and induce apoptosis in hepatocellular carcinoma [22]. Fellenberg et al [23].…”
Section: Discussionmentioning
confidence: 99%